50 Disproportionate incidence of neuroendocrine cervical cancer in minority populations – a study of 2, 046 patients. (13th November 2020) - Liao, C; Furey, K; Chan, C; Richardson, MT; Tran, K; Tian, C; Darcy, KM; Kapp, DS; Cohen, JG; Chan, JK
Abstract : Objectives: To determine the incidence of Neuroendocrine Cervical Cancer (NEC) in regards to age, race and stage at presentation. Methods: From 2001 to 2016, incidence rates of cervical cancer were calculated from United States Cancer Statistics with Surveillance, Epidemiology and End Results (SEER) Program. SEER*Stat and Joinpoint regression were used to calculate the incidence rate (per 100, 000 women) and average annual percent change (AAPC), adjusted for hysterectomy and pregnancy prevalence data from the Behavioral Risk Factor Surveillance System. Results: Between 2001–2016, Neuroendocrine Carcinoma of the cervix (NEC) was identified in 2, 046 (1%) patients of 200, 000 women with cervical cancer; of which, 1, 300 were White (63.5%), 332 Blacks (16.2%), 267 Hispanics (13.0%), and 35 Asians (5.9%) and 26 unidentified (1.3%). For all races, age-adjusted incidence of NEC increased from 0.067 per 100, 000 women in 2001 to 0.091 in 2016. Age-adjusted incidence was higher in minority populations compared to Whites (Blacks 0.11; Asians 0.092; Hispanics 0.086; Whites 0.075 per 100, 000). The incidence of NEC increased with age in both Hispanics and Blacks. The peaks in incidence for Blacks was significantly older at 80+yo (0.35 per 100, 000) compared to 60–64yo for Hispanics (0.2) and 35–39yo (0.14) for Whites. Compared to Squamous Cell Carcinoma, NEC patients were more likely to have distant disease at diagnosis (37.4% vs. 12.5%) and less localized disease (22.3% vs. 43.2%) after adjusting for race and age. Conclusion: Compared to Whites, Blacks and Hispanics have a significantly higher incidence of neuroendocrine carcinoma. Moreover, Hispanics have more advanced stage at presentation.